An Overview of Management Newborn Based on Apgar Score in Makassar City Hospital (Indonesian Contemporary Nursing Journal (ICON Journal), 2022)
Introduction: The Apgar Score assessment is carried out after the baby is born to assess the baby’s condition and determine the initial treatment measures to be taken. The aim of this research is to get a description of the treatment in newborns based on the Apgar score at the Makassar City Hospital. The sample was obtained as many as 256 babies born at the Makassar City Hospital. Method: This study used the quantitative design with descriptive methods. The instrument used are observation sheet based on data from medical records. Result: In this study, the results showed that babies born with an Apgar score of 7-10 at 1st minute did not require oxygen assistance (83,2%), and suctioning of the mucus was performed which generally used a bulb syringe (84%), all newborns with an Apgar score of 7-10 no resuscitation was performed. Conclusion: Our results suggest that newborns with an Apgar score of 0-3 undergo routine treatment such as loan suction using a suction cannula, provide positive pressure ventilation using a t-piece resuscitator and perform resuscitation measures. However it is important to monitor oxygen saturation before administering oxygen therapy. It is expected that the nurse/midwife will give treatment based on SOP and conform to the Apgar Score. For future researchers to examine the long-term effects of oxygen use in infants.
Keywords: Newborn; Apgar Score; Asphyxia